Fintech Ecosystem on Blockchain-Based Sukuk: Perspective of Al-Najjar's Maqāṣid Al-Shariah Concept - Iman, Aldi Khusmufa Nur; Zustika, Anisa Fadilah; Maghfiroh, Lailatul; Wahdati, Anis (Universitas Al-Qolam Malang, 2025)
The Fourth Industrial Revolution has had a significant impact on financial technology, one of which is the emergence of blockchain technology as a tool for sukuk issuance. This study aims to analyze the fintech ecosystem in blockchain-based sukuk using the Maqāṣid al-najjar theory approach, which include: faith, humanity, self, mind, welfare, social entities, wealth, and the environment. This study uses a qualitative methodology with a literature study approach. The results of the study indicate that sukuk based on blockchain technology are in line with seven of the eight basic principles set out in the Maqāṣid al-najjar framework. technology such as smart contracts, transparency of blockchain technology, efficiency of sukuk issuance, and safe and globally supportive accessibility. such as an example of one of the values of faith through Sharia compliance, humanity through efficiency and reduction of issuance costs, and wealth through the distribution of assets carried out safely and transparently. However, the environmental dimension is still not met in these values, due to the high energy consumption of blockchain, which is contrary to the Maqāṣid al-najjar theory of preserving the environment. This study concludes that blockchain technology-based sukuk is very much in line with the basic principles of Maqāṣid Al Najjar, such as increasing the efficiency and accessibility of Islamic financial instruments. However, to fully fulfill the eight elements of Maqāṣid sharia initiated by al najjar, efforts are needed to address environmental problems and challenges through the development and innovation of energy-efficient blockchain technology or other sustainable solutions